2022
DOI: 10.1038/s41536-022-00250-7
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic primed extracellular vesicles activate miR-455/SOX11/FOXO axis for cartilage regeneration and osteoarthritis treatment

Abstract: Osteoarthritis (OA) is the leading cause of disability worldwide. Considerable progress has been made using stem-cell-derived therapy. Increasing evidence has demonstrated that the therapeutic effects of BMSCs in chondrogenesis could be attributed to the secreted small extracellular vesicles (sEVs). Herein, we investigated the feasibility of applying engineered EVs with chondrogenic priming as a biomimetic tool in chondrogenesis. We demonstrated that EVs derived from TGFβ3-preconditioned BMSCs presented enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…In recent years, increasing research has indicated that exosome-derived miRNAs, as epigenetic factors, are associated with bone metabolism ( 44 46 ). Exosome-derived miRNAs play a role in regulating processes related to the development of the musculoskeletal system, including embryonic development, osteoblast differentiation, bone marrow mesenchymal stem cell osteogenesis, paraspinal muscle differentiation, and cartilage formation., and they are directly or indirectly involved in the development of AIS ( 47 49 ). Additionally, exosome-derived miRNAs are protected by the outer vesicle, allowing them to remain stable in the RNA enzyme-rich environment of the blood ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing research has indicated that exosome-derived miRNAs, as epigenetic factors, are associated with bone metabolism ( 44 46 ). Exosome-derived miRNAs play a role in regulating processes related to the development of the musculoskeletal system, including embryonic development, osteoblast differentiation, bone marrow mesenchymal stem cell osteogenesis, paraspinal muscle differentiation, and cartilage formation., and they are directly or indirectly involved in the development of AIS ( 47 49 ). Additionally, exosome-derived miRNAs are protected by the outer vesicle, allowing them to remain stable in the RNA enzyme-rich environment of the blood ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, the possibility to use EVs is gaining a growing consensus. As an example, EVs released by bone marrow MSCs exposed to TGFβ3, shown to contain the chondrogenic microRNAs miR-455, were reported to improve osteoarthritis symptoms and cartilage replacement by activating the SOX11/FOXO signal transduction pathway [ 52 ]. These EVs also exert immunosuppressive and anti-inflammatory activities, resulting in a microenvironment that favors tissue regeneration [ 53 ].…”
Section: Evs As a Tool To Support Musculoskeletal Healthmentioning
confidence: 99%
“…Alternatively, hydrogels can also be prepared first, and then mixed with the EVs solution to allow the adsorption of EVs into hydrogels [ 55 ]. The most often used hydrogel materials for EVs delivery include calcium alginate (Ca-Alg) [ 53 , 56 ], arginine-glycine-aspartate (RGD) [ 57 , 58 , 59 ], hyaluronic acid (HA) [ 55 , 60 , 61 , 62 ], chitosan (CS) [ 54 , 63 , 64 , 65 , 66 ], and gelatin methacrylate (GelMA) [ 34 , 52 , 67 , 68 ]. The synthesis of the hydrogel has been well documented in many reviews [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], and is not described in the current work.…”
Section: Synthesis Of Evs-based Hydrogelsmentioning
confidence: 99%
“…Sun et al [ 62 ] obtained EVs enriched with engineered miR-445 from transforming growth factor β3 (TGFβ3) pretreated BMSCs. The EVs were loaded into the gelatin–fibrinogen–HA–glycerol composite hydrogels by in situ polymerization, which were injected into rat knee joints.…”
Section: The Application Of Evs-loaded Hydrogels In Disease Treatmentmentioning
confidence: 99%